LEARNERS’ COMMUNICATION IMPEDIMENTS AND CLASSROOM REALITY: EXPLORING THE SHORT SHRIFT ATTRIBUTED TO VOCABULARY LEARNING - Soumia HADJAB (Ziglôbitha)
Abstract : The current study aimed to investigate EFL learners’ communication needs, to scrutinise teachers’ perceptions towards their learners’ communication hiccups, and to probe how classroom undertakings ally with improving the students’ communicative skill.An exploratory research was conducted at the Department of English Language and Literature, Sétif2 University, Algeria. The participants were: 30 first year students and 8 oral expression teachers. A needs analysis survey, a semi-structured interview, and classroom observation were the research tools used to attain the aims stated above. Quantitative data was analysed through the Statistical Package for the Social Sciences; and qualitative data was figured out via Thematic Analysis. The results reveal that both learners and teachers acknowledge that speaking is one of the cardinal skills to be elaborated; however, language students have a finite bulk of vocabulary knowledge, which is pivotal for both language learning/ acquisition and communicative ability. Further, the activities held in the EFL class do not replicate those found in authentic settings, and ‘aping of dialogues’ and the Initiation/ Response/ Feedback cycle prove to dominate classroom discourse. The ‘transmission-based model of teaching’ characterises classroom procedures and learners’ knowledge is chiefly evaluated by linguistic modes as answering teachers’ queries, constructing written assignments and sitting exams. A‘speaking programme to improve the oral production’ is an urgent need learners seek for. A programme where learners are trained to expand their awareness of themselves as learners. And to enhance as language users, one must have a cavernous understanding of the essence of the language being studied and the process of learning it. Keywords: vocabulary, communication hiccups, IRF (Initiation/ Response/ Feedback) cycle, speaking programme, learner training.